2014
DOI: 10.1155/2014/901428
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs as Potential Biomarker for Gastric Cancer by System Biological Analysis

Abstract: Gastric cancers (GC) have the high morbidity and mortality rates worldwide and there is a need to identify sufficiently sensitive biomarkers for GC. MicroRNAs (miRNAs) could be promising potential biomarkers for GC diagnosis. We employed a systematic and integrative bioinformatics framework to identify GC-related microRNAs from the public microRNA and mRNA expression dataset generated by RNA-seq technology. The performance of the 17 candidate miRNAs was evaluated by hierarchal clustering, ROC analysis, and lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…An interesting finding in this meta-analysis was that we did not include any articles that attached attention on multiple miRNAs with regard to OSCC, which may be a possible factor of the limited clinical effect. As expected, in recent sufficient studies, it indicated that a combination of miRNAs (generally 3–5 miRNAs) was more complete indicators than individual miRNAs in various cancers, such as breast cancer, 19 21 prostate cancer, 22 , 23 colorectal cancer, 24 26 gastric cancer, 27 29 lung cancer, 30 , 31 and pancreatic cancer. 32 Therefore, further studies about the comparative diagnosis effect between multiple miRNAs and individual miRNAs on OSCC are needed to be performed.…”
Section: Discussionsupporting
confidence: 76%
“…An interesting finding in this meta-analysis was that we did not include any articles that attached attention on multiple miRNAs with regard to OSCC, which may be a possible factor of the limited clinical effect. As expected, in recent sufficient studies, it indicated that a combination of miRNAs (generally 3–5 miRNAs) was more complete indicators than individual miRNAs in various cancers, such as breast cancer, 19 21 prostate cancer, 22 , 23 colorectal cancer, 24 26 gastric cancer, 27 29 lung cancer, 30 , 31 and pancreatic cancer. 32 Therefore, further studies about the comparative diagnosis effect between multiple miRNAs and individual miRNAs on OSCC are needed to be performed.…”
Section: Discussionsupporting
confidence: 76%
“…Nowadays, computational approaches based on systems biology and network science are well performed on detecting microRNA or gene signatures for the diagnosis and treatment of complex diseases such as cancers [ 15 , 16 ], diabetes [ 17 ] and neurodevelopmental disorders [ 18 ]. In particular, Zhang et al introduced a correlation and clustering based framework to identify microRNA-mRNA network modules for differentiating PPCa and MPCa subtypes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miRNAs have also been shown to target mRNAs in the coding region, 5′-UTR as well as promoter region. This sparked great interests in elucidating the dynamic roles of miRNA that may play in the development and progression of cancer, and led to the rapid expansion of this field 7 8 9 . According to miRBase Release 21 (June 2014), 2,588 unique mature human miRNAs have been identified 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%